Bioremediation of atrazine: recent advances and promises - Fan, Xuxiao; Song, Fuqiang (Journal of soils and sediments, 2014)
Purpose Atrazine is one of the most widely used herbicides to control broadleaf and grassy weeds for many crops in the world. Its contamination has become a growing public concern because atrazine is the most commonly detected pesticide in soil and groundwater. Studies have indicated that atrazine may cause damages to the central nervous system, endocrine system, and immune system. The aim of this review was to update our understanding of recent development of atrazine bioremediation for its improved application. Materials and methods Bioremediation, an economical and eco-friendly approach, has emerged as the most advantageous technique for cleaning up atrazine contamination in soil and water. A large number of atrazine-degrading bacteria and fungi have been isolated. The genetic pathways for atrazine remediation/detoxification have been well characterized in bacteria, fungi, and plants. Results and discussion To enhance bioremediation, transgenic microbes and plants expressing atrazine-degrading enzymes have been developed. Co-application of transgenic microbes and transgenic plants has been proposed to get synergistic effect for bioremediation of atrazine. Conclusions In summary, although effective bioremediation methods of atrazine removal have been successfully employed, it should be noted that there has been a series of disappointing failures, along with tremendous successes in the laboratory. Overall, future research should be geared toward narrowing the gaps between bioremediation in laboratory and environmental applications.